2000
DOI: 10.1074/jbc.m000021200
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Plus-strand Primer Selection, Removal, and Reutilization by Retroviral Reverse Transcriptases

Abstract: The ability of reverse transcriptase to generate, extend, and remove the primer derived from the polypurine tract (PPT) is vital for reverse transcription, since this process determines one of the ends required for integration of the viral DNA. Based on the ability of the RNase H activity of Moloney murine leukemia virus reverse transcriptase to cleave a long RNA/DNA hybrid containing the PPT, it appears that cleavages that could generate the plus-strand primer can occur by an internal cleavage mechanism witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
49
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 77 publications
2
49
0
Order By: Relevance
“…Despite the ability of reverse transcriptase to carry out DNA displacement synthesis at a nick (21,25,43), the PPT primer is not efficiently reutilized for additional plus-strand synthesis (19,37). A similar situation might arise when RNase H creates the PPT primer if RNase H were to make only a single cleavage at the Ϫ1/ϩ1 site.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Despite the ability of reverse transcriptase to carry out DNA displacement synthesis at a nick (21,25,43), the PPT primer is not efficiently reutilized for additional plus-strand synthesis (19,37). A similar situation might arise when RNase H creates the PPT primer if RNase H were to make only a single cleavage at the Ϫ1/ϩ1 site.…”
mentioning
confidence: 85%
“…An example is the generation of the PPT primer: RNase H efficiently generates the 3Ј end of the PPT primer by a specific cleavage within the PPT at the plus-strand origin, herein referred to as the Ϫ1/ϩ1 site. Importantly, this RNase H cleavage is sequence specific and can occur internally on an RNA-DNA hybrid without 5Ј end-directed binding (14,37). Sequence recognition directly contributes to RNase H specificity for at least two other sites as well.…”
mentioning
confidence: 99%
“…With respect to the 3Ј PPT, this mechanism creates 5Ј-terminal sequences of the double-stranded DNA for recognition by viruscoded integrase. Although selection and removal of the PPT primer have been accurately recapitulated in biochemical studies with wild type and mutant RT variants (7,20,(23)(24)(25)(26)(27)(28)(29)(30)(31), the structural basis for resistance to internal hydrolysis and specific cleavage at the PPT-U3 junction remains elusive. Analysis of a co-crystal of HIV-1 RT and a PPT-containing RNA/DNA hybrid (4) suggest that the altered groove width observed might not permit correct positioning of the RNA strand in the RNase H catalytic center, a notion put forward by studies of related RNA/DNA hybrids (32)(33)(34)(35)(36)(37)(38).…”
mentioning
confidence: 99%
“…Cleavage site specificity is required for proper generation and removal of the PPT (18,26,38,41,45,47,50,52,53,54,57,58,64,75). Previous studies have demonstrated that certain residues within the PPT and its overall helical structure are important determinants for specific cleavage and extension (21,26,33,41,51,55,60,63). The sites of plus-and minus-strand initiation are important because they ultimately define the ends of the full-length proviral DNA, which are recognized by the viral integrase (5,62; reviewed in reference 11).…”
mentioning
confidence: 99%